2021
DOI: 10.1111/aej.12533
|View full text |Cite
|
Sign up to set email alerts
|

Shaping efficiency of XP‐endo shaper and Mtwo instruments in long oval root canals: A micro‐CT study

Abstract: This study evaluated the shaping ability of XP-endo Shaper and Mtwo systems in long-oval-shaped canals of extracted human mandibular molars using micro-computed tomography (micro-CT). Images recorded before and after preparation were evaluated for morphometric measures regarding increase in canal volume, dentin removed, surface area, untouched walls and structure model index (SMI). Data were statistically analysed using the Mann-Whitney test with 5% of significance. On both groups, the root canal preparation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…XP-endo Shaper system was chosen for its better adaptation to the root canal anatomy as proposed by the manufacturer 7 , whereas the WaveOne Gold system was chosen because it is worldwide used and promotes a significant bacterial reduction within the root canal 1 . The preparations using both systems increased the root canal surface, which corroborates other studies assessing several automated systems 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 . Versiani et al 10 and Marques et al 14 found an increase of 10.8% and 11,3% respectively by using XP-endo Shaper files in long oval-shaped root canals, which are values close to ours, that is, 11.18%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…XP-endo Shaper system was chosen for its better adaptation to the root canal anatomy as proposed by the manufacturer 7 , whereas the WaveOne Gold system was chosen because it is worldwide used and promotes a significant bacterial reduction within the root canal 1 . The preparations using both systems increased the root canal surface, which corroborates other studies assessing several automated systems 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 . Versiani et al 10 and Marques et al 14 found an increase of 10.8% and 11,3% respectively by using XP-endo Shaper files in long oval-shaped root canals, which are values close to ours, that is, 11.18%.…”
Section: Discussionsupporting
confidence: 89%
“…Different techniques and instruments have had difficulties in preparing root canals as untouched areas are always left after instrumentation 2 , 4 , 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 . The present study assessed XP-endo Shaper and WaveOne Gold systems before and after additional manual instrumentation in the preparation of long oval-shaped root canals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have shown no significant difference in the preparation of oval canals using XP-endo Shaper (34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1 , An X-ray three-dimensional microscope (micro-CT) [ 9 , 10 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] is mainly composed of a micro-focus ray source system, a precision sample stage system, a high-resolution optocoupler detector, and a flat panel detector system. An X-ray three-dimensional microscope is an instrument developed based on the CT imaging principle.…”
Section: Introductionmentioning
confidence: 99%